Pengendalian Alih Fungsi Lahan Pertanian Berkelanjutan di Kecamatan Pallangga Kabupaten Gowa - Muhammad Sidratul Munthoha, Andi Alief; Syafri, Syafri; Idris Taking, Muhammad; Congge, Umar (Fakultas Teknik Universitas Bosowa, 2023)
The purpose of this study was to determine the pattern of distribution of agricultural land, the factors causing changes in the function of sustainable agricultural land and to control changes in the function of agricultural land, Pallangga District, Gowa Regency. This research uses quantitative methods. Based on the results of the analysis, it shows that the development of changes in land use in Pallangga District in 2019 was dominated by agricultural activities and dry land with a percentage of 54.49% and 27.90% respectively, while in 2022 there was a decline, where the use of agricultural land and land dry changed to 41.95% and 27.46%. As for residential land, it increased by 27.73%. Meanwhile, the factors that influenced changes in agricultural land use included: Land Requirement Factors, Social Factors, while economic factors and policy factors had little influence. Control over the conversion of agricultural land is carried out with a strategy of minimizing the opportunities for land conversion, controlling land conversion activities and providing instruments to control land conversion